Preliminary study of the antimalarial activity and toxicity of quercus infectoria (Manjakani) - Mohamad, Mira Nabila (Universiti Sains Malaysia, 2017)
Quercus infectoria or manjakani is traditionally used as an alternative medicine in a Malay culture in various applications. There is no scientific research available on the treatment of Plasmodium falciparum-infected erythrocytes using this plant. The objective of the study was to determine the in vitro antimalarial activity and toxicity of the Q. infectoria ethanol extract against chloroquine-sensitive (3D7) and chloroquine-resistant (Dd2) strains of P. falciparum. The toxicity and heavy metal tests were performed using Brine Shrimp Lethality Test (BSLT) and Atomic Absorption Spectrophotometry, respectively. The antimalarial activity of the extract was determined using malaria SYBR Green I-based fluorescence (MSF) assay. The plant extract was considered non-toxic according to the Mayer’s toxicity index (lethality concentration, LC50 - 1945.86 ± 1.97 ppm) and contained low amounts of heavy metals according to the CODEX standard (Pb = -0.085 ± 0.026 mg/L, Cr = 0.135 ± 0.005 mg/L, Zn - 0.348 ± 0.003 mg/L and Cd = 0.006 ± 0.039 mg/L). The extract inhibited 3D7 and Dd2 parasite growth with the IC50 values of 22.46 ± 8.85 pg/mLdan 18.41 ±4.17 pg / mL, respectively. The growth and development of the parasites were inhibited upon 24 and 48 hours treatments with the plant extract. In conclusion, the data show that the 0. infectoria ethanol extract has a great potential as an antimalarial candidate.